Botox injection for anal fissure management: case report - Gede Eka Rusdi Antara (DiscoverSys Inc., 2022)
Introduction: Anal fissure is shallow tear in the anoderm distal to dentate line which is considered most common proctologic condition. Anal fissure is generally located in the posterior midline. The symptoms include anal pain, spasm, and/or bleeding during defecation1. The pain can be so intense as to induce the patient to avoid defecation with consequent hardening of the feces and exacerbation of the problem2. Management of the anal fissure is improving diet and defecation habit, medical therapy and surgical therapy. The goal of medical treatment for chronic anal fissure is to temporarily reduce pressure of the anal canal to facilitate the healing of the fissure (“reversible sphincterotomy”), thereby reducing muscle tone. Intrasphincteric Botulinum Toxin A injection seems to be a reliable option. Case reports: two male patients were diagnosed with anal fissures, the patients complained of pain and spasm. They were treated with botulinum toxin type A (100 unit AllergenÒ), injected into three sites of the internal sphincter at 2, 5 and 8 o’clock. The symptoms relieved and the anal fissure healed within one month. There was no sign of relapse or incontinence during 12 months of follow-up. Conclusion: Botulinum toxin therapy can be considered as efficacious, effective and safe treatment for anal fissures. Keywords: anal fissure, botox, botulinum toxin, intrasphincteric